Model Diversifikasi Fungsi Subak sebagai Daya Tarik Ekowisata di Subak Sembung, Peguyangan, Kecamatan Denpasar Utara - I PUTU PUTRA WIGUNA; WAYAN SUDARTA; I KETUT SURYA DIARTA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2018)
A Model of Subak Diversifying Functions as an Attraction to Ecotourism in Subak Sembung, Peguyangan, North Denpasar Subak Sembung is one of the Subak in Denpasar which has a wide area of farming around 115 Ha. Subak Sembung has becoming an attraction to ecotourism since year of 2014. The Ecotourism in Subak Sembung was established as a water absorption area in Denpasar city. This was meant to keep motivating the farmers not to shift the function of that land. Currently, condition of the field has shown that Subak Sembung is now dealing with a threat of land shifting function because of its existance in the middle of Denpasar city, so the ecotourism in Subak Sembung was then created to further anticipate it. This research discussed about any Subak diversifying functions after the ecotourism in that area was established. It also described the models of its diversification as an attraction in Subak Sembung. The method of analysis used to explain the reseach problem was a descriptive qualitative analysis. That qualitative description was applied on the information received from some key speakers by Krama Subak or the admin of that ecotourism. The results showed that the role and function ofSubak brought up to an attranction for Subak Sembung ecotourism. The diversification of those roles and functions included religion ceremony that performed any rituals, therefore Subak could sell a culture in farming. The others were involving facilities operation and maintenance like building a trekking path along the rice field for tourists and also providing other supporting facilities along the area. The establishment of ecotourism was led by Badan Lingkungan Hidup (BLH) and PPLH that had constructed an ecotourism management in 2014. Nevertheless, there was also another issue found regarding with the lack of waste management and abence of share of direct income for the site. Therefore, as a suggestion, a contribution should be given especially to the Subak itself in the future because it would help to motivate the farmers to sustain the rice field area. The farmers should also be open-minded to accept a new innovation,meanwhile both sides of the ecotourism and Subak need to be alert to follow up with the rubbish issue around the area. It is also suggested that Denpasar government in line with the management of ecotourism should give a direct contribution for Subak sustainability in the future.